Numerical prediction of ground vibrations induced by LPG boiling liquid expansion vapour explosion (BLEVE) inside a road tunnel - Cheng, Ruishan; Chen, Wensu; Hao, Hong; Li, Jingde (Pergamon Press Ltd., 2023)
Accidental boiling liquid expansion vapour explosions (BLEVEs) caused by the bursting of liquified petroleum gas (LPG) tank inside a tunnel can induce vibrations of its surrounding geological media and threaten the stability of adjacent tunnels and structures. Therefore, it is essential to understand the characteristics of vibrations induced by LPG BLEVEs inside the tunnel for the safety design of its adjacent structures. Owing to the difficulty in effectively predicting the LPG BLEVE loads, the current practice usually employs equivalent methods, e.g., the TNT-equivalency method, in LPG BLEVE load predictions for structural response analysis, which may lead to inaccurate response predictions. This study compares ground vibrations induced by a BLEVE inside an arched road tunnel with those induced by its equivalent TNT explosion via high-fidelity numerical simulations. The results demonstrate that the frequency of BLEVE-induced vibrations is lower than that induced by the TNT explosion at the same scaled distance. The intensity of LPG BLEVE-induced vibrations at relatively small-scaled distances is lower than that of TNT explosion-induced vibrations at the same scaled distance, but becomes higher after a certain scaled distance because of the relatively low attenuation rate. In addition, parametric analysis is conducted to evaluate the effects of various factors on the characteristics of LPG BLEVE-induced ground vibrations. It is found that the surrounding rock type, the rock porosity, and the cover depth of the tunnel have more significant influences than the concrete grade of the tunnel lining. The recommendation for the tunnel design is also given based on the intensity and frequency characteristics of BLEVE-induced vibrations.